Mengevaluasi Kinerja Perbankan Syariah Berdasarkan Keuangan di Bank BRI Syariah Melalui Rasio Keuangan dan Laporan Keuangan - Rusmini, Rusmini; cahyono, Dimas (INAIFAS Press, 2023)
In the context of the global meeting of the sharia financial industry, assessing the performance of sharia-based financial institutions is crucial for evaluating the stability and growth of the sector. This abstract focuses on analyzing the financial performance of BRI sharia bank, as one of the main players in the Indonesian sharia banking industry. By using financial report data for the 2018, 2019 and 2020 periods, this analysis explores the bank's financial performance through aspects such as profitability ratios, liquidity, solvency and bank activity and health. It is hoped that the results will provide in-depth insight into the contribution of BRI sharia banking to the growth and stability of the sharia banking financial sector. Through this analysis, it is hoped that a very strategic and relevant recommendation can be found to improve the performance of sharia banking, especially from this discussion which is based on BRI sharia banking.